Oxford textbook of palliative medicine - Cherny, Nathan I.; Fallon, Marie; Kaasa, Stein; Portenoy, Russell K.; Currow, David (Oxford University Press, 2015)
Written by an established, comprehensive, multidisciplinary focused, internationally-recognized team, the fifth edition has been fully revised and brought up to date with the inclusion of recent developments in the speciality, to ensure that it retains its reputation as the definitive reference on palliative care.